Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.4317/jced.2.e169
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effectiveness of different endodontic irrigants on the reduction of Enterococcus faecalis in root canals

Abstract: Objective: To compare the reduction of E. faecalis counts in root canals produced by irrigation with distilled water, hydrogen peroxide, sodium hypochlorite, chlorhexidine, and combinations of solutions, in vitro. Study Design: Study sample included sixty mandibular premolar teeth mounted in dental stone. Root canals were prepared using crown down technique under distilled water irrigation. Specimens were sterilized overnight by ethylene oxide gas. Each canal was completely filled up with the E. faecalis suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(24 reference statements)
0
6
0
1
Order By: Relevance
“…Studies conducted by Jayahari et al have concluded that passion fruit [7] extracts were sensitive to Enterococcus faecalis bacteria. In accordance with the study done by Vinay Kumar G et al, the contact time for 2ml of irrigants was taken as 10 minutes followed by 1ml of sterile saline and similar study by vijayakumar S et al used 5 ml of the [15,16] tested irrigant for a contact time of 5 minutes.…”
Section: Discussionmentioning
confidence: 96%
“…Studies conducted by Jayahari et al have concluded that passion fruit [7] extracts were sensitive to Enterococcus faecalis bacteria. In accordance with the study done by Vinay Kumar G et al, the contact time for 2ml of irrigants was taken as 10 minutes followed by 1ml of sterile saline and similar study by vijayakumar S et al used 5 ml of the [15,16] tested irrigant for a contact time of 5 minutes.…”
Section: Discussionmentioning
confidence: 96%
“…10 Some of the other pioneer studies have also shown the presence of bacteria during intracanal dressings, before and after instrumentation. 11,12 In the present study, we used 5.25% sodium hypochlorite (NaOCl), 2% chlorhexidine (CHX), 200 mg/ mL N-Acetylcysteine (NAC) and sterile distilled water as an irrigating solution. We observed that planktonic bacterial count was significantly higher in group IV in which sterile distilled water was used as compared to groups I-III.…”
Section: Discussionmentioning
confidence: 99%
“…Vijaykumar et al . [20] and Whelan et al . [21] demonstrated that metronidazole was effective against B. fragilis , which is in agreement with the results obtained in the current study.…”
Section: Discussionmentioning
confidence: 99%